1994
DOI: 10.1246/bcsj.67.2311
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition of COS

Abstract: Thermal decomposition of COS was investigated by shock tubes between 1140—3230 K. The decay of COS and S was monitored by IR emissions and atomic resonance absorption spectrometry (ARAS) coupled with laser flash photolysis technique, respectively. The rate constants for the reactions COS + M → CO + S + M (1) and COS + S → CO + S2 (2) were determined as k1 = (4.07 ± 1.83) × 10−10exp (−257 ± 24kJ/RT), T: 1900—3230 K and k2 = (3.91 ± 1.18) × 10−11exp (−28.3 ± 0.9 kJ/RT) cm3 molecule−1 s−1, T: 1140—1680 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 6 publications
5
28
0
Order By: Relevance
“…2 in which lines of various types are drawn for only the range of temperature investigated. Our data of k 1 increase from ͑2.7± 0.5͒ ϫ 10 −15 cm 3 molecule −1 s −1 at 298 K to ͑1.04± 0.19͒ ϫ 10 −12 cm 3 molecule −1 s −1 at 985 K, showing a distinct deviation from a linear Arrhenius form, but connecting satisfactorily data for T Ͼ 860 K by Shiina et al, 1 Oya et al, 2 and Woiki et al 3 and those for T = 233-445 K by Klemm and Davis. 6 Fitting our results alone yields an expression for the rate coefficient in the range of 298ഛ T /Kഛ 985:…”
Section: A Experimental Rate Coefficient Below 250 Torrsupporting
confidence: 90%
See 2 more Smart Citations
“…2 in which lines of various types are drawn for only the range of temperature investigated. Our data of k 1 increase from ͑2.7± 0.5͒ ϫ 10 −15 cm 3 molecule −1 s −1 at 298 K to ͑1.04± 0.19͒ ϫ 10 −12 cm 3 molecule −1 s −1 at 985 K, showing a distinct deviation from a linear Arrhenius form, but connecting satisfactorily data for T Ͼ 860 K by Shiina et al, 1 Oya et al, 2 and Woiki et al 3 and those for T = 233-445 K by Klemm and Davis. 6 Fitting our results alone yields an expression for the rate coefficient in the range of 298ഛ T /Kഛ 985:…”
Section: A Experimental Rate Coefficient Below 250 Torrsupporting
confidence: 90%
“…When combined with data for T Ͼ 860 K reported by Oya et al, 2 Woiki et al, 3 and those for T = 233-445 K by Klemm and Davis., 6 we derive a general expression k 1 ͑T͒ = ͑6.63 ± 0.33͒ ϫ 10 −20 T 2.57±0. 19 ϫexp͓− ͑1180 ± 120͒/T͔ cm 3 molecule −1 s −1 ,…”
Section: A Experimental Rate Coefficient Below 250 Torrmentioning
confidence: 85%
See 1 more Smart Citation
“…The curvature of the calibration curve was determined assuming the single-exponential decay of S atom concentrations by the pressure-independent reference reaction, 3,8 The obtained calibration curve for the high-pressure range is shown in Figure 1, where those at lower pressure range used in the previous study are shown for comparison. The curvature of the calibration curve was determined assuming the single-exponential decay of S atom concentrations by the pressure-independent reference reaction, 3,8 The obtained calibration curve for the high-pressure range is shown in Figure 1, where those at lower pressure range used in the previous study are shown for comparison.…”
Section: Methodsmentioning
confidence: 99%
“…Time evolutions of S and O atoms measured under the same experimental condition are shown in Figure 4. S atoms produced in the photolysis showed single exponential decay and the net rate for the reaction S ϩ O 2 was determined by subtracting the contribution of the reaction S ϩ COS (typically 4 -18% of the whole rate) [8,30]. O atoms increase initially via the reaction (2) but then decrease caused by the reaction, O ϩ COS : CO ϩ SO.…”
Section: Reaction Of S(mentioning
confidence: 99%